Influence of working length and foraminal enlargement on foramen morphology and sealing ability - Juliana Melo Silva; Gustavo A Brandão; Emmanuel João Nogueira Leal Silva; Alexandre Augusto Zaia (Wolters Kluwer Medknow Publications, 2016)
Aim: The present study evaluated the influence of the working length and foraminal enlargement on the sealing ability and anatomy of the apical region of the root. Materials and Methods: Fifty-five roots were divided into three groups: G1, instrumentation 1 mm short of the major foramen; G2, instrumentation in the limit of the apical foramen; and G3, instrumentation 1 mm beyond the foramen. All groups were prepared using nickel-titanium rotary files and obturated with AH Plus and Gutta-percha. Photomicrographs were taken using a scanning electron microscopy (SEM) before instrumentation, after instrumentation with each file, and after root canal filling. Moreover, bacterial microleakage with Enterococcus faecalis was performed. Results: The results were analyzed using Mann-Whitney, Friedman, Kruskal-Wallis and Kaplan-Meier tests at a significance level of 5%. The cemental canal was uninstrumented in G1. No statistical differences regarding foramen deviation was observed when compared G2 and G3 (P > 0.05). SEM analysis showed that G2 and G3 resulted in good apical foramen obturation. Microleakage showed no statistically significant differences between all of the groups tested. Conclusions: Under the conditions of this study, it can be concluded that foramen enlargement resulted in more apical deviation; however, no differences in bacterial microleakage was observed among the experimental groups.